A Comprehensive Correlation of Clinicopathologic Prognostic Factors in Malignant Adult Renal Tumors: A Single Institutional Study - Sobiya M AYESHA; Swetha SIVAKUMAR; Rahul DEVRAJ; Rajsekhar SHANTAPPA; Ranganath RATNAGIRI; Meher Lakshmi KONATAM; Shantveer G UPPIN; Tara Roshni PAUL; Megha S UPPIN (Federation of Turkish Pathology Societies, 2024)
Objective: To study the clinicopathologic prognostic parameters of malignant adult renal tumors as these have poor over-all survival (OS) and show frequent metastasis. Material and Methods: This was a retrospective analysis of the clinical and pathologic features of malignant renal tumors in adult patients from January 2011 to December 2020. All the tumors were studied with respect to age, clinical presentation, tumor type/subtype, histologic grade (WHO/ISUP grading system), TNM stage and presence of necrosis. Correlation of histopathologic features and survival analysis was done using Kaplan-Meier survival curves and Cox-regression analysis. Results: A total of 257 cases were included in the study period including 253 renal cell tumors of which clear cell renal cell carcinoma accounted for 69.3%. The age of the patients ranged from 20 to 87 years (median-52 years). The overall survival significantly reduced with increasing histologic grade, stage, and presence of necrosis. The comparison between the histological subtypes was not statistically significant. Univariate Cox-regression analysis found significant hazard ratio with increasing age, size, histologic grade (G4 vs G1), stage, and presence of necrosis. The correlation of OS with histological subtypes was not significant. Multivariate analysis also showed increased hazard ratio with increasing age, size, grade, and stage. However, the P-value was significant only for age. Conclusion: Clear cell renal cell carcinoma was the commonest type of adult renal tumor. Older age at presentation, larger tumor size, presence of necrosis, and higher histologic grade and stage were associated with poor prognosis in these patients.